2006
DOI: 10.1002/cbdv.200690113
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Oil of Lippia alba: Analysis of Samples from French Overseas Departments and Review of Previous Works

Abstract: This paper contains new data on the chemical composition of the essential oil of Lippia alba (Mill.) N. E. Brown, as well as an overview of the available literature. Although the composition of the essential oil of this species is well-documented, discrepancies between the reported results suggest that many chemotypes and morphotypes exist. The analysis of essential oils obtained from the leaves of samples from three different locations in the French Overseas Departments (French Guiana, Martinique, and two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 28 publications
3
35
0
8
Order By: Relevance
“…A representation of the sample compositions, in the plane formed by the first two principal components, revealed the presence of four groups of essential oils (Figure): group I was formed exclusively by carvone and limonene-rich L. alba oils, group II consisted of citral and trans-β-caryophyllene-rich oils that corresponded to the L. alba, L. citriodora and L. dulcis species, group III contained carvacrol, thymol and pcymene-rich oils of the L. origanoides and L. micromera species and group IV comprised L. origanoides oils in which p-cymene was more abundant than carvacrol and thymol, but there were no detectable amounts of thymol methyl ether. Thus, the PCA analysis showed that L. alba and L. origanoides belonged to two different chemotypes, a fact that was already reported for such species (Hennebelle et al 2006, Stashenko et al 2008. Table I contains the results of the antiprotozoal and mammalian cell activities for the 19 essential oils examined.…”
Section: Resultssupporting
confidence: 58%
“…A representation of the sample compositions, in the plane formed by the first two principal components, revealed the presence of four groups of essential oils (Figure): group I was formed exclusively by carvone and limonene-rich L. alba oils, group II consisted of citral and trans-β-caryophyllene-rich oils that corresponded to the L. alba, L. citriodora and L. dulcis species, group III contained carvacrol, thymol and pcymene-rich oils of the L. origanoides and L. micromera species and group IV comprised L. origanoides oils in which p-cymene was more abundant than carvacrol and thymol, but there were no detectable amounts of thymol methyl ether. Thus, the PCA analysis showed that L. alba and L. origanoides belonged to two different chemotypes, a fact that was already reported for such species (Hennebelle et al 2006, Stashenko et al 2008. Table I contains the results of the antiprotozoal and mammalian cell activities for the 19 essential oils examined.…”
Section: Resultssupporting
confidence: 58%
“…alba occurs in various regions of Colombia (Durán et al 2007) and although the antifungal activity of some essential oils of this plant have been evaluated in other countries (Duarte et al 2005, Hennebelle et al 2006, in Colombia the biological activities of the L. alba chemotypes have not yet been fully elucidated. The aim of this study was to evaluate the chemical composition, cytotoxic effect and antifungal activity of essential oils of L. alba, as well as some of their components, from two regions of Colombia.…”
mentioning
confidence: 99%
“…11,12 The species is also notable for essential oil production and the monoterpenes citral (neral and geranial), linalool, limonene, carvone, camphor, 1,8-cineole, tangetenona, g-terpineno and estragole are reported as major constituents. 1,13 Qualitative and quantitative variations in the chemical composition of the essential oil, besides genotype, geographical origin, soil and weather factors and techniques of extraction, are used to discriminate chemotypes of L. alba. [14][15][16] According to Hennebelle et al, 13 besides the existence of different morphotypes of L. alba, the plant also has seven chemotypes which are characterized by different major constituents in their essential oils.…”
Section: Introductionmentioning
confidence: 99%
“…1,13 Qualitative and quantitative variations in the chemical composition of the essential oil, besides genotype, geographical origin, soil and weather factors and techniques of extraction, are used to discriminate chemotypes of L. alba. [14][15][16] According to Hennebelle et al, 13 besides the existence of different morphotypes of L. alba, the plant also has seven chemotypes which are characterized by different major constituents in their essential oils. 13 Later on, Mesa-Arango et al 10 suggested the existence of at least twelve chemotypes of this species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation